A theology of traumatic affect: a political and religious engagement - Kim, Alice (Lexington Books/Fortress Academic, 2025)
"Alice Kim constructs A Theology of Traumatic Affect by employing affect and trauma theories conjointly. The interconnectedness of individuals is established, which in turn uncovers the social dimensions of all traumatic experiences. A collective engagement makes bearing witness and holding the space for prophetic public imagination possible"--